The Role of Bone Marrow in Baseline Investigations for Advanced Intraocular Retinoblastoma - Huma Zafar, Mahwish Faizan, Asma Mushtaq, Shabana Choudhary, Javeria Fatima, Amber Goraya, Samina Zaman, M. Ashwin Reddy (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the rationale for bone marrow biopsy/aspiration as a part of a routine systemic workup in advanced intraocular retinoblastoma (RB) in relation to high-risk histopathological post-enucleation features. Methods: A retrospective observational study was conducted at the Department of Pediatric Hematology and Oncology of the Children’s Hospital, Lahore, Pakistan. Data regarding demographics, clinical presentations, staging workup, and treatment strategies of all the newly diagnosed retinoblastoma cases registered at our centre from January 2018 to December 2019 were collected. Statistical analysis was performed using IBM SPSS statistics version 22. Results: Of the 61 patients, 41 (67%) showed unilateral disease, while bilateral and trilateral involvement was found in 17 (28%) and three (5%) cases, respectively. The mean age of presentation in our cohort was 25 months (median: 24 months; range: <1–72 months). Amongst 81 eyes (61 patients), tumours were limited to an intraocular location in 54 eyes (46 patients). In this group, 42 eyes (38 patients) underwent enucleation. Adverse histopathology was found only in nine (23.68%) patients. None of the patients with the intraocular disease, with or without adverse histopathological features in enucleated eyes, were found to have bone marrow (BM) involvement. For 15 patients with extraocular disease, five (33%) patients were found to have bone marrow involvement based on initial investigations. Conclusion: Our study did not show any correlation between bone marrow positivity and advanced intraocular groups D/E RB. Therefore, BM evaluation can be avoided in this subset of patients with retinoblastoma at presentation, while stage III and IV patients (International Retinoblastoma Staging System IRSS) must be evaluated for metastasis. This will reduce the risks of biopsy to the patients and the burden on services. Keywords: Retinoblastoma, Bone Marrow Involvement, Intraocular disease.